Reducing Sexual risk Behaviors and Intentions among Rural African American Youth - Natasha De Veauuse Brown (Georgia Southern University, 2017)
Background: In spite of dramatic declines in teen pregnancy and childbearing in every state and amongst all racial groups, progress to-date remains unbalanced and disparities persist. Blacks, Hispanics, and youth residing in southern states or rural areas continue to experience the highest teen pregnancy rates in the nation. In an effort to enhance protective factors that help youth avoid behaviors placing them at risk for pregnancy, between September 2011 and May 2013, a public school district in rural southeast U.S. implemented an evidence-based youth development program designed to address these issues. Methods: A single-group, repeated measures design was employed to assess changes over time in past sexual risk behaviors, intentions regarding future behaviors, use of contraceptives, and pregnancy. The main questions answered were: does the program make a difference in the lives of youth involved, and to what extent? To answer these questions, participants completed brief selfadministered surveys during the first and last sessions of the intervention (pre-/post-intervention surveys). Results: 447 predominantly African American (98%) students in grades 8-12 were enrolled; 94% completed the program. There were significant improvements in participants' self-reported behaviors and intentions. For instance, when asked about their sexual activity during the three months before the pre-test, 69.0% of the students surveyed had sex at least once, but only 47.6% at post. Of those, 48.8% at pre and 58.2% at post reported having used a condom; 52.9% (pre) versus 69.6% (post) used some form of birth control. Conclusions: Students participating in this youth development program reported reductions in sexual risk behaviors and greater intentions to engage in safer sex practices in the future. Among the many lessons learned was the importance of offering incentives throughout the program's duration to retain participants for the 9-month, 25-session intervention period. Key words: sexual risk behaviors, youth, rural